GREEN PRODUCTIVITY TO INCREASE THE PRODUCTIVITY OF SUGARCANE FARMERS WITH COBB-DOUGLASS METHOD - Marodiyah , Inggit (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Sugarcane is a crop that requires a number of processing steps from planting to harvesting. Green productivity is a viable option to increase the productivity and sustainability of sugarcane. Various planting methods, management strategies (fertilisation), insect/pest and disease management options as well as management of adverse climatic conditions and waste management that not only improve soil fertility and sugarcane productivity are environmentally friendly and safe for the environment. Productivity in the sugarcane farming environment requires improvement so that the sugarcane management process does not adversely affect the environment. The purpose of this study is to determine the factors that affect productivity and recommendations for improving green productivity. Cobb Douglass method to determine the factors in sugarcane farming that affect the sugarcane management process and green productivity is a strategy used to increase productivity and reduce the environmental impact of sugarcane fields. The results of this study found that the output elasticity value of sugarcane farm labour input symbolized (β) in the 2021-2022 period was smaller than the input of raw materials (α), which was 0.39 in units of million rupiah. Based on this, it can be concluded that the input that has the greatest influence on the productivity of sugarcane farmers is labour, as evidenced by the smallest elasticity value, which means that it has a large influence on productivity. So that to increase green productivity is to reduce the cost of expenditure on labour by maximising working time